The Role of The Tanoto Foundation as an Philanthropic International Organization in Supporting the improvement of Quality Education in Indonesia - Nidham, Dhayfullah Ilyasa; Septyana Rahayu, Dini (UNIDA GONTOR, 2023)
Education is one essential aspect of human life that is endless. The quality of human resources can be seen from a person's education. Of course, quality education can increase future generations competitiveness and that has the potential for the progress of a nation. To achieve SDGs Quality Education, the role of various sectors is needed, one of which is a philanthropic organization. In this study, the author took the research object of the Tanoto Foundation as an international philanthropic organization that plays a role in supporting the achievement of SDGs Quality Education in Indonesia. As members of Indonesian Philanthropy, they are engaged in education which supports improving of the quality of education in Indonesia. This study uses a descriptive qualitative method to explain the role of the Tanoto Foundation as an international philanthropic organization in improving the quality of education in Indonesia by using two concepts, namely the concept of philanthropy and the concept of Sustainable Development Goals ( SDGs). By using deductive reasoning which is from general things to specific things. This research aims to explain, in achieving the targets of the SDGs, the need for roles from all sides, not only from the government. As for data collection techniques, the authors use literature review techniques , scientific journals , books, documentation, magazines, internet media, reports and observations. Based on the results of this study the Tanoto Foundation, with its three main programs, namely: SIGAP, PINTAR and TELADAN play a role in improving the quality of education in Indonesia by referring to the targets and indicators from the fourth point regarding Quality Education in Indonesia.